Kekerasan dalam Konflik Kelapa Sawit di Kalimantan Tengah (Konsep Tiga Dimensi Kekerasan Johan Galtung) - Elia Damayanti; Yuliana (Jurnal Ilmu Politik dan Studi Sosial Terapan, 2025)
The implications of a democratic society are freedom and equality. If this becomes more prominent, then conflict is normal because freedom and equality will give space to differences in views, even opposing each other. However, conflict becomes unusual if it becomes violent. Likewise with the palm oil conflict between palm oil plantation companies and the community in Central Kalimantan. This article aims to take a general picture of violent palm oil conflict incidents using Johan Galtung's 3-dimensional concept of violence, including structural violence, direct violence, cultural violence. Through primary data and secondary data support regarding palm oil conflicts in Central Kalimantan. The results of the identification show that these 3 dimensions of violence were found in the palm oil conflict in Central Kalimantan, including poverty and plasma complaints, criminalization and shootings to death, as well as fear of the police and structural violence in the name of security and order.